Screening of Risk of Type 2 Diabetes Mellitus in Sungai Buluh Village, Padang Pariaman - Devia Putri Lenggogeni; Hema Malini; Esi Afriyanti; Reni Prima Gusty; Rahmi Muthia; Elvi Oktarina (Warta Pengabdian Andalas, 2024)
Diabetes mellitus (DM) type 2 is a non-communicable disease, and the incidence continues to increase. Various factors can increase the incidence of type 2 DM, but many people lack the awareness to determine risk factors and the efforts that need to be made to reduce the risk of type 2 DM. This community service aims to conduct health examinations and determine the risk level of DM type 2 in Sungai Buluh, Padang Pariaman, West Sumatra. This community service activity includes health examination, determining risk levels of risk type 2 DM, and personal education to reduce the risk of type 2 DM. The instrument used to determine the risk of type 2 DM is the Finnish Diabetes Risk Score (FINDRISC). Type 2 DM screening showed that most people had a slightly increased risk 37 people (45.6%), low-risk 26 people (32.1%), high-risk 13 people (16.1%) and very high-risk five people (6.2%). It is hoped that health centers will carry out risk level screening and education on reducing the risk of type 2 DM as a planned and structured activity to increase public awareness to prevent and reduce the risk of type 2 DM.